Way adaptable D-NUCA caches. (9th August 2010) - Bardine, Alessandro; Comparetti, Manuel; Foglia, Pierfrancesco; Gabrielli, Giacomo; Prete, Cosimo
Non-uniform cache architecture (NUCA) aims to limit the wire-delay problem typical of large on-chip last level caches: by partitioning a large cache into several banks, with the latency of each one depending on its physical location and by employing a scalable on-chip network to interconnect the banks with the cache controller, the average access latency can be reduced with respect to a traditional cache. The addition of a migration mechanism to move the most frequently accessed data towards the cache controller (D-NUCA) further improves the average access latency. In this work we propose a last-level cache design, based on the D-NUCA scheme, which is able to significantly limit its static power consumption by dynamically adapting to the needs of the running application: the way adaptable D-NUCA cache. This design leads to a fast and power-efficient memory hierarchy with an average reduction by 31.2% in energy-delay product (EDP) with respect to a traditional D-NUCA. We propose and discuss a methodology for tuning the intrinsic parameters of our design and investigate the adoption of the way adaptable D-NUCA scheme as a shared L2 cache in a chip multiprocessor (CMP) system (24% reduction of EDP).